Post-accident damage identification based on vibration measurements applied to masonry structures - Ramos, Luís F. (2008)
The present paper aims at damage assessment of masonry structures in an early stage. Two replicates of historical constructions were built in virgin state, one arch with 1.5 m span and one shear wall of 1 m2. Afterwards, progressive damage was applied and sequential modal identification analysis was performed in each damage stage, aiming at finding adequate relations between changes in dynamical behaviour and internal crack growth. During the dynamic tests, accelerations and strains were recorded in many points of the replicates. Comparisons between different techniques based on vibrations measurements were made to evaluate which methods are the most suitable for identifying damage in masonry constructions. All the knowledge emerged from the experimental tests was then applied to two case studies: a masonry clock tower, in the northern part of Portugal, and the church of Monastery of Jerónimos, in Lisbon. The two monuments have installed a dynamic monitoring system, where the environmental effects are measured. The paper presents the results of the arch model simulation and the results of the case study of Jerónimos Monastery church.